Regular Exercise Modulates the dfoxo/dsrebp Pathway to Alleviate High-Fat-Diet-Induced Obesity and Cardiac Dysfunction in Drosophila. - Yan, H.; Ding, M.; Peng, T.; Zhang, P.; Tian, R.; Zheng, L. (International journal of molecular sciences, 2023)
Obesity is a prevalent metabolic disorder associated with various diseases, including cardiovascular conditions. While exercise is recognized as an effective approach for preventing and treating obesity, its underlying molecular mechanisms remain unclear. This study aimed to explore the impact of regular exercise on high-fat-diet-induced obesity and cardiac dysfunction in Drosophila, shedding light on its molecular mechanisms by identifying its regulation of the dfoxo and dsrebp signaling pathways. Our findings demonstrated that a high-fat diet leads to weight gain, fat accumulation, reduced climbing performance, and elevated triglyceride levels in Drosophila. Additionally, cardiac microfilaments in these flies exhibited irregularities, breakages, and shortening. M-mode analysis revealed that high-fat-diet-fed Drosophila displayed increased heart rates, shortened cardiac cycles, decreased systolic intervals, heightened arrhythmia indices, reduced diastolic diameters, and diminished fractional shortening. Remarkably, regular exercise effectively ameliorated these adverse outcomes. Further analysis showed that regular exercise reduced fat synthesis, promoted lipolysis, and mitigated high-fat-diet-induced cardiac dysfunction in Drosophila. These results suggest that regular exercise may mitigate high-fat-diet-induced obesity and cardiac dysfunction in Drosophila by regulating the dfoxo and dsrebp signaling pathways, offering valuable insights into the mechanisms underlying the beneficial effects of exercise on obesity and cardiac dysfunction induced by a high-fat diet.